Energy-related contaminants in subterranean waterbodies: The role of geocolloids on facilitated and hindered transport - Mustafa E.S. Akbulut; Younjin Min (Next Sustainability)
The examination of energy byproduct transport and associated contaminant dynamics in geosystems and aquatic ecosystems is important for evaluating the ramifications of energy generation and consumption. This article critically reviews contemporary studies on the influence of aqueous geocolloids in modulating the transport kinetics of energy-related contaminants within subterranean hydrological systems. The primary objectives of this work are to: i) introduce the morphological and physicochemical properties of prevalent geocolloid varieties and explain their formation mechanisms, ii) outline the mechanistic pathways by which geocolloids alter contaminant transport dynamics, and iii) analyze the ramifications for applications such as coal mining, hydraulic fracturing, chemically-enhanced oil recovery, and radionuclide storage. A systematic literature review was conducted, synthesizing findings from experimental investigations, computational simulations, and field observations. These studies reveal that geocolloids can facilitate or impede contaminant mobility by modifying parameters such as effective diffusivity, rheological properties, and interfacial deposition kinetics across multiple spatiotemporal scales. The presence of geocolloids introduces non-linear complexities in contaminant fate and transport that go beyond conventional advection-dispersion models. These topics have significant implications for risk assessment methodologies and remediation strategies related to energy production and waste management in geological formations, particularly in terms of colloid-facilitated contaminant transport and its impact on the vulnerability of waterbodies and geosystems.